Extraction of Fronto-orbital Shower Hook through Transcranial Orbitotomy. Issue 2 (June 2014) - Elia, Maxwell D.; Gunel, Murat; Servat, Juan J.; Levin, Flora
Transorbital foreign bodies threaten both the integrity of the globe and the brain. We present an unusual case of a penetrating right frontal lobe-orbital metallic shower hook. Extensive intracranial involvement necessitated transcranial orbitotomy allowing for the removal of the object without loss of the globe.